1996
DOI: 10.1007/bf02054692
|View full text |Cite
|
Sign up to set email alerts
|

Pouchitis following pelvic pouch operation for ulcerative colitis

Abstract: The risk for pouchitis was highest during the initial six-month period. Cumulative risk leveled off after two years but was substantial (51 percent) at four years. Less than 10 percent of patients had severe, chronic pouchitis, and only two patients (1.3 percent) had their pouches removed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
122
1
8

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(140 citation statements)
references
References 19 publications
9
122
1
8
Order By: Relevance
“…Also, those with extensive disease were the lightest smokers, whereas those with healthy colons were the heaviest smokers. Finally, current smokers have a lower incidence of pouchitis following coloproctectomy with ileal reservoir when compared with non-smokers [30,31] . In contrast, intriguing new data by Aldhous et al [29] showed that current and non-smokers had an almost identical age at onset (31.1 vs 29.4 years) and this was delayed only in ex-smokers (46.5 years).…”
Section: Effect Of Smoking and Its Cessation On Clinical Course And Ementioning
confidence: 93%
“…Also, those with extensive disease were the lightest smokers, whereas those with healthy colons were the heaviest smokers. Finally, current smokers have a lower incidence of pouchitis following coloproctectomy with ileal reservoir when compared with non-smokers [30,31] . In contrast, intriguing new data by Aldhous et al [29] showed that current and non-smokers had an almost identical age at onset (31.1 vs 29.4 years) and this was delayed only in ex-smokers (46.5 years).…”
Section: Effect Of Smoking and Its Cessation On Clinical Course And Ementioning
confidence: 93%
“…As the majority of patients develop acute pouchitis within the first year after IPAA [65] , VSL#3® containing 4 strains of Lactobacillus, 3 Bifidobacterium species, and Streptococcus www.wjgnet.com salivarius subsp. Thermophillus was evaluated for the primary prophylaxis for the initial episode of pouchitis.…”
Section: Treatmentmentioning
confidence: 99%
“…For the maintenance of remission and the prevention of chronic pouchitis, VSL#3 probiotic proved to be more effective than placebo. Chronic pouchitis which requires maintenance suppressive therapy and common leads to pouch failure has been reported in approximately 9% to 20% of all surgeries [11]. Refractory pouchitis may significantly influence the patients' quality of life.…”
Section: Discussionmentioning
confidence: 99%